Position tracking and global localization of mobile terminals in cellular networks - Khalaf-Allah, Mohamed; Kyamakya, Kyandoghere (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2007)
Dead reckoning (DR) via direction and distance could provide an accurate way of maintaining location information for mobile terminals when loss of GPS signals occurs. Furthermore, DR would provide reliable solutions in indoor/outdoor transitions, street canyons, and heavy tree canopies where GPS information is almost always inapplicable. Thus, DR is a desirable option for security and commercial applications that value position information. This paper describes and investigates how DR could provide accurate and reliable positioning using radio profile databases and map-matching. The proposed technique solves both the position tracking and global localization problems, so that mobile terminal localization could be achieved in case of GPS outage or even without any GPS information at all respectively. © 2007 IEEE.
Created from Fastlane, Scopus look-up